Aplikasi Pembelajaran dengan Menggunakan Bahan Ajar Berbasis Teori Van Hiele Berbantuan Software Geometer's Sketchpad pada Kemampuan Representasi Matematis Siswa - Budi Hari Priyanto; Abduloh Abduloh; Mokhammad Ridwan Yudhanegara (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
Geometry Transformation courses is contained visuals (diagrams, graphs, tables), images, equations, and interpretations. So that in order to understand it, students must have good mathematical representation ability. Furthermore, this article examines the comparison of the improvement of students' mathematical representation abilities in Transformation Geometry courses. Comparisons were made on three groups selected purposively with subject matching techniques. The results showed that in the 95% confidence level there was a difference in the increase in students' mathematical representation ability between those who received learning by using van hiele theory-based teaching materials assisted by Geometer's Sketchpad software, and students who learned the van hiele theory assisted by Geometer's Sketchpad software and students who obtained learning with constructivism theory.